Erianin alleviates diabetic retinopathy by reducing retinal inflammation initiated by microglial cells via inhibiting hyperglycemia‐mediated ERK1/2–NF‐κB signaling pathway. Issue 11 (31st July 2019) - Zhang, Tianyu; Ouyang, Hao; Mei, Xiyu; Lu, Bin; Yu, Zengyang; Chen, Kaixian; Wang, Zhengtao; Ji, Lili
Abstract : Blood‐retinal barrier (BRB) breakdown is a typical event in the early stage of diabetic retinopathy (DR). This study aims to elucidate the protection of erianin, a natural compound isolated from Dendrobium chrysotoxum Lindl, against DR development. Erianin alleviated BRB breakdown and rescued the reduced claudin1 and occludin expression in retinas from streptozotocin‐induced diabetic mice. Erianin reduced microglial activation, ERK1/2 phosphorylation, NF‐κB transcriptional activation, and the elevated TNF‐α expression both in vitro and in vivo. ERK1/2 inhibitor U0126 abrogated NF‐κB activation in D‐glucose‐treated BV2 cells. Erianin reduced cellular glucose uptake, and molecular docking analysis indicated the potential interaction of erianin with glucose transporter (GLUT)1. GLUT1 inhibitor (STF31) reduced the activation of the ERK1/2‐NF‐κB signaling pathway. Coculture with D‐glucose‐stimulated microglial BV2 cells and with TNF‐α stimulation both induced inner BRB and outer BRB damage in human retinal endothelial cells and APRE19 cells, but erianin improved all these damages. In summary, erianin attenuated BRB breakdown during DR development by inhibiting microglia‐triggered retinal inflammation via reducing cellular glucose uptake and abrogating the subsequent activation of the downstream ERK1/2‐NF‐κB pathway. Moreover, erianin also alleviated BRB damage induced by TNF‐α released from the activated microglia.—Zhang, T., Ouyang, H., Mei, X., Lu, B., Yu, Z., Chen, K., Wang, Z., Ji, L. Erianin alleviates diabetic retinopathy by reducing retinal inflammation initiated by microglial cells via inhibiting hyperglycemia‐mediated ERK1/2‐NF‐κB signaling pathway. FASEB J. 33, 11776‐11790 (2019). www.fasebj.org